Proyek Menggapai “Islamic Intellectualism”: Ikhtiar Mencari Alternatif - Yusdani (Direktorat Pondok Pesntren Universitas Islam Indonesia, 2020)
The following aritcle tries to trace the way out of the problem dichotomic regarding religion and science relation. The moslem scholars’ response and the solution toward the problem can be classified into islamization and integration. But in the context of islamization still emerges the debates and pros and conts among moslem scholars. As the best solution of this problem according to critical moslem scholars and also that of the founding fathers of Islamic University of Indonesia - UII - between reiligion ang science is the integration. The basic aspect of the integration based on the philosophy of science including of ontology, epistemology and axiology. As the consequent, Islam as revelation can contribute to three pilars of philosophy of science and the building theory of Islamic science must accomodate empirical data and science must consider revelation. Departing from the integration, the direction of Islamic sciences reconstruction based on culture strategy. This strategy needs comprehensive and systematics Islamic horizon that does not only in accordance with circumstance but also denotes the demand of Islamic teaching to express Islam itself as charity that in harmony with time, functional and humantarian Islam. Only by this, it is possible to produce Islamic Intellectualism in Islamic universities